EVALUASI PENGUKURAN KINERJA DENGAN IT BALANCED SCORECARD STUDI PADA DEPARTBMEN INFORMATION & COMMUNICATION SERWCES PT DARYA.VARIA LABORATORIA TBK - , Bobby Gulliano ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Information technology (IT) at this point has become an integral part of many organizations. Therefore a good synergy needed between business units with IT departments, so that existing technology/information systems resources can transformed into supporting company's performance realization. Business unit leaders in PT. Darya-Varia Laboratories TBK (DVL) argues that the performance of the Information & Communication Services (ICS) department has not been able to contribute to the organization in line with expectations. On the other hand, ICS department argues that a lot of software has been made, and complained that the performance built so far not was not recognized by the business units. Therefore this thesis study aims to: 1. Evaluating the current performance measurement of ICS department from the point of view of IT Balanced Scorecard concept. 2. Identifying factors that support and hinder the implementation of current performance measurement of ICS department. 3. Designing future performance measurement of ICS department from the point of view of IT Balanced Scorecard concept. A literature study was conducted on the concept of strategic management, performance measurement, balanced scorecard concept introduced by Robert S. Kaplan and David P. Norton, strategy map and IT Balanced Scorecard by Wim Van Grembergen, Ph.D. The study was conducted by interviewing top management of DVL and conduct focused group discussion, attended by entire section head in the ICS department. Data were also collected from the company's internal documents and ICS internal documents, especially documents on the ICS department assessment and performance measurement. Analysis performed on the data collected, then current ICS department performance measurement evaluated from the point of view of IT balanced scorecard concept. Factors that support and hinder the implementation of the current ICS department performance measurement identified. Then, future ICS department performance measurement crafted by the concept of IT Balanced Scorecard, based on the interviews and focus group interviews result. Conclusions drawn and suggestions for further research suggested.